Perception of Ideal Body Image as Self-Disclosure in Early Adult Women - Nur Afiah (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2022)
The ideal body shape is a picture of how the shape and size of the body are proportional. Every individual has a different body concept about his body. Several research results reveal each individual has different perceptions related to body image. The difference in behavior can be seen from the pattern of social relations carried out. Adult women still pay attention to appearance and often compare their body shape with others, including weight. This study describes the body image of early adult women, which includes three components, namely perception, attitude, and behavior. This study uses a qualitative method with a phenomenological approach. The number of research subjects was two early adult women with ages between 22-35 years. The results showed that between subjects 1 and 2 had differences in perceiving body image. Meanwhile, attitudes and behavior have the same results regarding body image. They are feeling satisfied when having an ideal body weight, feeling dissatisfied when the size of certain areas of the body is larger than others. The implications of being satisfied and dissatisfied in both subjects cause anxiety that impacts behavior. Both subjects control eating more, exercise, and use attributes that can support their appearance, so they are confident when socializing with other people.